Morphological study of the infraorbital gland of the male barking deer, Muntiacus muntjak - Adnyane, I Ketut Mudite; Abu Bakar @ Zakaria, Md Zuki; Mohamed Mustapha, Noordin; Wahyuni, Sri; Agungpriyono, Srihadi (Academic Journals, 2011)
The morphology of the infraorbital gland of the barking deer (Muntiacus muntjak) was examined using lectin histochemistry, immunohistochemistry and scanning electron microscopy. The glands consisted of sebaceous and apocrine glands, with proportion of apocrine glands was larger than the sebaceous gland. Sebaceous glands consisted of many lobules with polyhedral cells. The apocrine glands were lined by cuboidal to columnar cells with typical apical protrusions. Seven lectins applied showed various binding intensities in the sebaceous and apocrine glands. Peanut agglutinin (PNA) and soybean agglutinin (SBA) were strongly positive in the sebaceous gland, while the others lectins showed various positive reactions from weak to strong intensities in the membrane and cytoplasm areas. In the apocrine gland portion, positive reaction with various intensities was observed for all the seven lectins. In the myoepithelial cells of the apocrine glands, positive reactions were found in moderate intensity only for SBA and dolichos biflorus agglutinin (DBA). Immunoreactivity for a-smooth muscle actin was observed in the myoepithelial cells in the basal membrane of the apocrine gland. These findings suggest that the secretion of the infraorbital gland of the barking deer contains lipid from the sebaceous gland and glycoconjugates secreted by both the sebaceous and apocrine glands.